Memory for fearful faces across development: specialization of amygdala nuclei and medial temporal lobe structures - Pinabiaux, Charlotte; Pannier, Lucie; Chiron, Catherine; Rodrigo, Sebastian; Jambaque, Isabelle; Noulhiane, Marion (Frontiers in Human Neuroscience, 2013)
Enhanced memory for emotional faces is a significant component of adaptive social interactions, but little is known on its neural developmental correlates. We explored the role of amygdaloid complex (AC) and medial temporal lobe (MTL) in emotional memory recognition across development, by comparing fMRI activations of successful memory encoding of fearful and neutral faces in children (n=12; 8-12 years) and adolescents (n=12; 13-17 years). Memory for fearful faces was enhanced compared with neutral ones in adolescents, as opposed to children. In adolescents, activations associated with successful encoding of fearful faces were centered on baso-lateral AC nuclei, hippocampus, enthorhinal and parahippocampal cortices. In children, successful encoding of fearful faces relied on activations of centro-mesial AC nuclei, which was not accompanied by functional activation of MTL memory structures. Successful encoding of neutral faces depended on activations in anterior MTL region (hippocampal head and body) in adolescents, but more posterior ones (hippocampal tail and parahippocampal cortex) in children. In conclusion, two distinct functional specializations emerge from childhood to adolescence and result in the enhancement of memory for these particular stimuli: the specialization of baso-lateral AC nuclei, which is associated with the expertise in processing emotional facial expression, and which is intimately related to the specialization of MTL memory network. How the interplay between specialization of AC nuclei and of MTL memory structures is fundamental for the edification of social interactions remains to be elucidated.